The relevance of instruction, language exposure and age for heritage children's development of complex morphosyntax: triangulating data from narratives and cloze-tests - Torregrossa, Jacopo; Flores, Cristina; Rinke, Esther (Frontiers in Language Sciences, 2025)
For children speaking a heritage language, the onset of schooling may induce a shift in dominance of language exposure from the heritage language to the societal language. This shift may affect the acquisition of morphosyntactic structures in the heritage language, especially of those that, due to their morphosyntactic complexity, tend to be acquired in school age even by monolingual children. The present study investigates the morphosyntactic abilities of 59 children aged 7 to 16 living in Switzerland, speaking European Portuguese as heritage language and German as societal language. Children's morphosyntactic abilities were measured using a written cloze-test and a narration task. By triangulating the results from both tasks, we examined which factors influenced morphosyntactic development in the heritage language, focusing on the role of task type, age, amount of heritage language instruction and variety of heritage language exposure at home, and their interaction with the complexity of the target structures. The results revealed a clear effect of complexity, with more complex structures being produced less accurately, and a task effect, with narratives yielding fewer accurate productions than cloze-tests. Additionally, we found a general effect of age, particularly for less complex structures. Crucially, the amount of years attending heritage language classes emerged as a key factor in the mastery of the most complex structures, whereas the variety of exposure to the heritage language at home showed no significant effect. The results are discussed in terms of the importance of exposure to formal registers of European Portuguese, provided by the heritage language courses in Switzerland, for the consolidation of more complex morphosyntactic abilities.